Presence of Mycobacterium avium subsp. paratuberculosis in Environmental Samples Collected on Commercial Dutch Dairy Farms - Eisenberg, Susanne W. F. (American Society for Microbiology (ASM), 2010)
Mycobacterium avium subsp. paratuberculosis, the causative agent of Johne's disease in cattle, was identified in settled-dust samples of Dutch commercial dairy farms, both in the dairy barn and in the young stock housing. Bioaerosols may play a role in within-farm M. avium subsp. paratuberculosis transmission.